Intervensi Berbasis Internet untuk Menghadapi Kehilangan dan Berduka: Literature Review - Yosep, Iyus; Damayanti, Siti Nur; Radinka, Evania Altsa; Rahayu, Nindy Sofiani; Hikmat, Rohman; Mardhiyah, Ai (Jurnal Kesehatan Metro Sai Wawai, 2023)
Introduction: Loss is a state in which a person is detached from something that existed before, with the possibility of being partially or completely absent. Each individual will respond and take a different amount of time to accept a loss. Internet-based remote intervention can be an alternative face-to-face intervention for psychological therapy for people who have experienced loss. Purpose: To explore internet-based interventions in reducing loss and grieving symptoms using the rapid review method. Methods: This literature review uses CINAHL, PubMed, Science Direct, and Cochrane as article search databases, with the year of publication ranging from 2012-2022, and the main focus refers to individuals who have experienced loss and bereavement. Results: The search results, there were 386 articles, and the selection results obtained 6 articles which show that there are several interventions, such as exposure and behavioral activation, Cognitive-behavioral therapy, and healthy experience after a loss, that are effective in dealing with the problem of grieving for individuals who have experienced the loss of a partner, child, death due to suicide of a loved one and other forms of other disadvantages by using the internet. Conclusion: Internet-based interventions have the potential for nurses to modify nursing care in reducing the impact of loss and grieving on victims by providing a comprehensive online-based implementation so that it can be accessed more easily by nurses and patients. Latar Belakang: Kehilangan adalah keadaan di mana seseorang terlepas dari sesuatu yang ada sebelumnya, dengan kemungkinan sebagian atau seluruhnya tidak ada. Setiap individu akan merespon dan membutuhkan waktu yang berbeda untuk menerima sebuah kehilangan. Intervensi jarak jauh berbasis internet dapat menjadi alternatif intervensi tatap muka untuk terapi psikologis bagi orang yang mengalami kehilangan. Tujuan: Studi ini bertujuan mengeksplor intervensi berbasis internet dalam mengurangi gejala kehilangan dan berduka dengan metode rapid review. Metode: Literatur review ini menggunakan CINAHL, PubMed, Science Direct, dan Cochrane sebagai database pencarian artikel, dengan rentang tahun publikasi 2012-2022, dan fokus utama mengacu pada individu yang pernah mengalami kehilangan dan berduka. Hasil: Hasil pencarian terdapat 386 artikel, dan hasil seleksi mendapat 6 artikel yang menujukkan terdapat beberapa Intervensi seperti exposure and behavioral activation, Cognitive-behavioral therapy, serta healthy experience after a loss, efektif mengatasi masalah berduka bagi individu yang pernah mengalami kehilangan pasangan, anak, kematian akibat bunuh diri orang yang dicintai dan bentuk kerugian lainnya dengan menggunakan internet. Simpulan: intervensi berbasis internet menjadi potensi bagi perawat untuk memodifikasi asuhan keperawatan dalam menurunkan dampak kehilangan dan berduka pada korban dengan memberikan implementasi secara komprehensif berbasis online agar dapat diakses lebih mudah oleh perawat dan pasien.